2019
DOI: 10.1186/s12889-019-6999-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of school-based skills-training programs promoting mental health in adolescents: a study protocol for a randomized controlled study

Abstract: Background Adolescence is a period of elevated stress sensitivity, which places adolescents at increased risk of developing mental health problems such as burnout, depression, anxiety, and externalizing problems. Early intervention of psychological needs and low-threshold care addressing such needs may prevent this dysfunctional development. Schools may provide an important environment to identify and address psychological needs. The aim of this protocol is to describe the design of a study aiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 89 publications
0
25
0
2
Order By: Relevance
“…SHS students typically perceive more pressure to succeed and must adapt to new academic workloads, school expectations, and social relationships. Thus, they are especially prone to experiencing anxiety and depression [ [30] , [31] , [32] ]. Moreover, our findings suggested that being a rural resident, which may relate to a lower level of family income, was a risk factor for depression and anxiety [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHS students typically perceive more pressure to succeed and must adapt to new academic workloads, school expectations, and social relationships. Thus, they are especially prone to experiencing anxiety and depression [ [30] , [31] , [32] ]. Moreover, our findings suggested that being a rural resident, which may relate to a lower level of family income, was a risk factor for depression and anxiety [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 outbreak occurred during the course of this study, which provided an ideal opportunity to investigate the impact of the COVID-19 pandemic on indicators of mental health in adolescents. The effectiveness study examined two school-based skills-training programs in which adolescents enrolled by self-selection, addressing social skills or skills to deal with performance anxiety 22 . The small-group skills-training programs consisted of seven sessions of 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…As the COVID-19 outbreak occurred during the course of this study, it provided an ideal opportunity to collect data about COVID-19 related concerns in adolescents. This evaluation study investigated the effectiveness of school-based skills-training programs, in which secondary school students enrolled by self-selection (van Loon et al, 2019). The current sample is a subsample, consisting of all adolescents that were included in the effectiveness study in February 2020.…”
Section: Study Design Participants and Proceduresmentioning
confidence: 99%